1982
DOI: 10.1007/bf00276593
|View full text |Cite
|
Sign up to set email alerts
|

X-Autosome translocations: Cytogenetic characteristics and their consequences

Abstract: To define the principal characteristics of X-autosome translocations, the authors present a study of 105 cases, five of which are personal observations. The autosomal pairs 15, 21, and 22 are affected by t(X-Aut) more often than would be expected. The distribution of breakpoints on the X chromosome does not differ significantly from the expected distribution. The analysis of different patterns of inactivation seems to confirm that the inactivation could occur at random, but would be followed by a cellular sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(95 citation statements)
references
References 75 publications
7
87
0
1
Order By: Relevance
“…Such homology likely generates a physical association between the sex vesicle or "XY body" (64,65) and the short arm of chromosome 15; physical association likely also occurs during metaphase (66). Sequence homology between repetitive DNA in chromosome 15 (and the other acrocentric chromosomes: 13, 14, 21, and 22) and in the X chromosome may also help generate a physical association (67); this may cause the excess of translocations involving the X chromosome and chromosomes 15, 21, and 22 (68). Entanglement may underlie the susceptibility of chromosome 15 to karyotypic abnormalities (69).…”
Section: Discussionmentioning
confidence: 99%
“…Such homology likely generates a physical association between the sex vesicle or "XY body" (64,65) and the short arm of chromosome 15; physical association likely also occurs during metaphase (66). Sequence homology between repetitive DNA in chromosome 15 (and the other acrocentric chromosomes: 13, 14, 21, and 22) and in the X chromosome may also help generate a physical association (67); this may cause the excess of translocations involving the X chromosome and chromosomes 15, 21, and 22 (68). Entanglement may underlie the susceptibility of chromosome 15 to karyotypic abnormalities (69).…”
Section: Discussionmentioning
confidence: 99%
“…In Gallus domesticus also, cytological evidence suggests that ZW gonosomes undergo non-homologous pairing in Z-autosome translocations (Solari et al, 1988 (Gustavsson et al, 1989). In that case as well as in the present translocation, the male was sterile, which is a common phenomenon in this type of translocation in man and mouse (reviewed by Mattei et al, 1982;Searle, 1982). According to Lifschytz and Lindsley (1972), the inactivation of the X chromosome is essential for normal spermatogenesis, which means that autosomal material translocated to the X chromosome interferes with X chromosome inactivation.…”
mentioning
confidence: 54%
“…At least at the cytological level, X inactivation can spread over quite long distances, into autosomal material, in both murine and human X;autosome translocations (e.g., see Disteche et al 1979;Mattei et al 1982;Keitges and Palmer 1986). In addition, ectopic copies of the mouse Xist gene can lead to inactivation of at least some autosomal loci (Lee and Jaenisch 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the phenomenon of X-inactivation progression has been linked cytologically to the timing of DNA synthesis. Using this difference in the timing of DNA synthesis, late-replication banding analyses of X;autosome translocations in both mouse and human have revealed that translocated autosomal material becomes later replicating compared with its intact autosomal counterpart and thus appears more like the adjacent inactive X chromosome (Eicher 1970;Disteche et al 1979;Mattei et al 1982;Keitges and Palmer 1986). Additionally, latereplication studies have suggested that the spreading of inactivation into autosomal sequences may be incomplete and discontinuous (Disteche et al 1984;Keitges and Palmer 1986;Schanz and Steinbach 1989).…”
Section: Introductionmentioning
confidence: 99%